Microbial Character Related Sulfur Cycle under Dynamic Environmental Factors Based on the Microbial Population Analysis in Sewerage System - Dong, Qian; Shi, Hanchang; Liu, Yanchen (Frontiers in Microbiology, 2017)
The undesired sulfur cycle derived by microbial population can ultimately causes the serious problems of sewerage systems. However, the microbial community characters under dynamic environment factors in actual sewerage system is still not enough. This current study aimed to character the distributions and compositions of microbial communities that participate in the sulfur cycle under the dynamic environmental conditions in a local sewerage system. To accomplish this, microbial community compositions were assessed using 454 high-throughput sequencing (16S rDNA) combined with dsrB gene-based denaturing gradient gel electrophoresis (DGGE). The results indicated that a higher diversity of microbial species was present at locations in sewers with high concentrations of H2S. Actinobacteria and Proteobacteria were dominant in the sewerage system, while Actinobacteria alone were dominant in regions with high concentrations of H2S. Specifically, the unique operational taxonomic units could aid to characterize the distinct microbial communities within a sewerage manhole. The proportion of sulfate-reducing bacteria (SRB)，each sufur-oxidizing bacteria (SOB) were strongly correlated with the liquid parameters (DO, ORP, COD, Sulfide, NH3-N), while the Mycobacterium and Acidophilic SOB (M&A) was strongly correlated with gaseous factors within the sewer, such as H2S, CH4 and CO. Identifying the distributions and proportions of critical microbial communities within sewerage systems could provide insights into how the microbial sulfur cycle is affected by the dynamic environmental conditions that exist in sewers and might be useful for explaining the potential sewerage problems.